2014
DOI: 10.1158/1055-9965.epi-14-0683
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations in Classical Hodgkin Lymphoma: A Systematic Review and Insights into Susceptibility Mechanisms

Abstract: Both targeted and genome-wide studies have revealed genetic associations for susceptibility, prognosis, and treatment-induced secondary malignancies and toxicities in classical Hodgkin lymphoma (cHL). This review gives a systematic and comprehensive overview of significant associations and places them into a biologic context. The strongest susceptibility polymorphisms have been found for the human leukocyte antigen (HLA) genes. These associations are specific for cHL overall or for subgroups based on tumor cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 72 publications
0
32
0
1
Order By: Relevance
“…Linkage studies in HL have identified both HLA class I (for Epstein-Barr virus [EBV]1) and class II (for EBV2) risk, and protective alleles and haplotypes. 10,11 Beyond HLA, linkage studies in CLL, 38 HL, 39 and WM 40 have not definitively identified genes with large effects, and there are no published studies in FL, DLBCL, or other NHL subtypes. For CLL, significant linkage was identified at 2q21.2, which contains the chemokine receptor (CXCR4) gene and for which rare coding mutations have been identified.…”
Section: Linkage Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Linkage studies in HL have identified both HLA class I (for Epstein-Barr virus [EBV]1) and class II (for EBV2) risk, and protective alleles and haplotypes. 10,11 Beyond HLA, linkage studies in CLL, 38 HL, 39 and WM 40 have not definitively identified genes with large effects, and there are no published studies in FL, DLBCL, or other NHL subtypes. For CLL, significant linkage was identified at 2q21.2, which contains the chemokine receptor (CXCR4) gene and for which rare coding mutations have been identified.…”
Section: Linkage Studiesmentioning
confidence: 99%
“…Also, the International Haplotype Map 46 and later the 1000 Genomes 47 projects, which catalog human genetic variation, became available as a reference and allowed "tagging" of genes and gene regions to take advantage of linkage disequilibrium (LD) to efficiently cover all of the common genetic variations for more comprehensive genotyping studies. 43 Although many studies of candidate genes have been published [7][8][9]11,48 , most findings have failed to replicate likely due to study design, bias from population stratification (ie, confounding by race or ethnicity), small sample size (low power), uncontrolled multiple testing (leading to false-positive associations), and unrealistic expectations in our ability to choose variants and genes. 49 The most robust findings have been for an LTA-TNF haplotype with DLBCL (P 5 2.93 3 10 ; and certain HLA alleles in class I (including HLA-A*01 and *02) with EBV1 HL and class II (including HLA-DRB1) with EBV2 HL.…”
Section: Genetic Association Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] Other non-HLA susceptibility loci have been identified through GWAS. [13][14][15] The identification of genes with major susceptibility effects has been more difficult. A study of a family with a reciprocal translocation between chromosomes 2 and 3 segregating with HL led to the identification of a disruption in the gene KLDHC8B, which codes for a midbody kelch protein, hypothesized to disrupt cytokinesis thereby promoting tumorigenesis.…”
mentioning
confidence: 99%